DISTRIBUSI JAMUR ASPERGILLUS FLAVUS PADA PETIS UDANG YOGYAKARTA - Yuliana Prasetyaningsih; Fitri Nadifah; Ika Susilowati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Indonesian tropical climate is a country and rich in marine products. Shrimp petis is a fermented products of shrimp. Shrimp petis is stored for too long risk for overgrown microorganisms. Therefore, during storage by a factor of humidity, shrimp petis can be polluted and overgrown by the fungus Aspergillus species. Fungus Aspergillus flavus commonly known as the cause of contamination of various types of food stored. Aflatoxin are toxins produced by fungi Aspergillus flavus. Aflatoxins can invade the central nervous system, some of which are carcinogenic cause cancer of the liver, kidneys, and stomach. The study objective was to determine the growth of the fungus Aspergillus flavus on various brands of shrimp paste are sold in supermarkets and traditional markets. Methods This study is a descriptive method of research objects shrimp paste with different brands sold in supermarkets and traditional markets with a single variable, namely the growth of Aspergillus flavus. The data obtained were analyzed descriptively using SPSS 17.0. Research shows the growth of the fungus Aspergillus flavus on various brands of shrimp paste are sold in supermarkets and traditional markets. The percentage growth of the fungus Aspergillus flavus on various brands of shrimp paste is 20% of the 10 samples identified shrimp paste.Keywords: Petis shrimp, Aspergillus flavus, aflatoxin.